2013
DOI: 10.1093/occmed/kqt036
|View full text |Cite
|
Sign up to set email alerts
|

Physician health programmes and malpractice claims: reducing risk through monitoring

Abstract: Background Physician health programmes (PHPs) are peer-assistance organizations that provide support to physicians struggling with addiction or with physical or mental health challenges. While the services they offer are setting new standards for recovery and care, they are not immune to public debate and criticism since some have concerns about those who are enrolled in, or have completed, such programmes and their subsequent ability to practice medicine safely. AimsTo examine whether medical malpractice clai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…PHPs in the USA were developed keeping in mind that early detection of potentially impaired physicians protects patients and saves physicians’ careers, and legal battles may be avoided by addressing these performance problems from a clinical perspective, instead of waiting for a crisis that necessitates disciplinary action 50. Brooks et al 51 found that physicians who were enrolled in a PHP showed a 20% lower malpractice risk after monitoring than a matched cohort. The high prevalence of Canadian studies on outcomes for dyscompetence in our review could perhaps be explained by the pioneering position Canada has had in peer assessment programmes.…”
Section: Discussionmentioning
confidence: 99%
“…PHPs in the USA were developed keeping in mind that early detection of potentially impaired physicians protects patients and saves physicians’ careers, and legal battles may be avoided by addressing these performance problems from a clinical perspective, instead of waiting for a crisis that necessitates disciplinary action 50. Brooks et al 51 found that physicians who were enrolled in a PHP showed a 20% lower malpractice risk after monitoring than a matched cohort. The high prevalence of Canadian studies on outcomes for dyscompetence in our review could perhaps be explained by the pioneering position Canada has had in peer assessment programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Another non-punitive approach to reducing malpractice payments was reported by Brooks et al [5]. Under examination was the use of Physician Health Programs (PHPs), peerassistance organizations that provide support to physicians struggling with addiction, or with physical or other mental health challenges.…”
Section: Reducing Physician Errorsmentioning
confidence: 99%
“…The Federation of State Physician Health Programs developed in recognition of a need highlighted by the American Medical Association (AMA) for objective and consistent monitoring and treatment of physicians with a wide range of health conditions. Data from CPHP suggest that physicians who had been monitored by CPHP for any reason had lower malpractice risk than the general population of physicians in Colorado [61]. When this finding is combined with the previous data on the decrease in the number of mandated referrals and increase in number of voluntary referrals when confidential services were made available, the way forward would seem clear.…”
Section: Peers and Other Stakeholdersmentioning
confidence: 81%